Global Trends In Digital Business: The Role of Artificial Intelligence, Big Data and The Platform Economy In Technology Startups In Indonesia - Icin Quraysin; Aan Desian; Aninda Aninda Balqis; Raditia Wibowo; Putriana Putriana (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze global trends in digital business through the role of artificial intelligence, big data, and the platform economy in technology startups in Indonesia. The research approach uses a descriptive qualitative method with the help of NVivo software to analyze data from interviews, observations, and documentation. The study was conducted from November 2025 to January 2026, involving startups from the e-commerce, fintech, edutech, and other digital service sectors. The results show that artificial intelligence contributes to improving operational efficiency, customer service automation, and transaction security. Big data plays a crucial role in strategic decision-making, consumer behavior analysis, and determining more accurate marketing strategies. Meanwhile, the platform economy has proven effective in expanding markets, increasing user connectivity, and creating scalable business models. However, Indonesian startups still face challenges such as limited digital talent, high technology implementation costs, intense market competition, and data protection issues. This study concludes that the integration of artificial intelligence, big data, and the platform economy is a strategic factor in strengthening the competitiveness of Indonesian startups in the global digital economy era. Support from an innovation ecosystem, adaptive regulations, and multi-stakeholder collaboration are needed for sustainable startup growth.